"Y a medida que el trabajo de la muerte avanzaba, y el aire se volvía más calmado, los ruidos de la artillería pesada parecían sacudir los techos de las iglesias sobre las aterrorizadas gentes que se reunían en ellas" : la otra guerra de la independencia (Estudios de Historia de España, 2016)
The Guerra de la Independencia, according to the traditional Spanish historiography, or The Peninsular Wars, the name given to that event by the English historians, is outlined as one of those moments when the English- Spanish relationships achieve a special strenght. From that fighting together against the same enemy, some literary works emerge and many more diaries and accounts written by officials or mere soldiers of the British Army which can be considered a valuable source of anecdotes, descriptions and appreciations worth analysing. It is, in this case, a compilation of personal experiences, most of the times very painful, with opinions of Spain and Portugal that reveal a condescending attitude
Keywords: Independence War; Accounts; Officials